CSC563: Artificial Intelligence Programming Paradigms / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2018)
This course will expose students to the goals and methods of artificial intelligence programming. The overview techniques of logic programming will be made in four stages: declarative, procedural, advanced and meta-programming. One programming language used in artificial intelligence will be taught.